2004
DOI: 10.1080/14767050412331283148
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus secondary to group B streptococcal meningitis

Abstract: Group B hemolytic streptococcus (GBS) is the most common cause of neonatal sepsis and meningitis. However, hydrocephalus as a presentation of neonatal GBS meningitis has not been reported. We report herein the case of a 23-day-old male infant who presented with significant hydrocephalus and subtle seizures, without a febrile episode, due to GBS meningitis. The infant needed a 3-week course of antibiotics, a ventriculoperitoneal shunt and anticonvulsant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…17 Age <2 years is considered an important prognostic factor for poor outcome of children with bacterial meningitis. 18,19 The younger age of patients have higher incidence of bacterial meningitis with neurologic complication, especially the newborn. 20 However, our study found that younger age and preterm delivery (birth history) may not be the risk factor for hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…17 Age <2 years is considered an important prognostic factor for poor outcome of children with bacterial meningitis. 18,19 The younger age of patients have higher incidence of bacterial meningitis with neurologic complication, especially the newborn. 20 However, our study found that younger age and preterm delivery (birth history) may not be the risk factor for hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…All previously described infants were treated with ventriculoperitoneal shunts, as was our patient (7). The outcome of infants with ventriculitis is variable, some patients do not survive, several develop neurological sequelae, and some have normal age-appropriate development (5,7,(9)(10)(11).…”
Section: Discussionmentioning
confidence: 88%
“…Eleven cases of ventriculitis without meningitis, including three patients with a meningomyelocele, have been described in the literature (5)(6)(7)(8)(9)(10)(11). All patients presented before the age of 10 weeks with feeding difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported in children with viral and other bacterial meningitis. 3 We report an unusual association of acute hydrocephalus in a 6-year-old girl with Group A Streptococcal meningitis and provide the results of a comprehensive literature review on acute CNS complications and neurological outcome in children 17years and under.…”
Section: Introductionmentioning
confidence: 99%
“…The Cerebrospinal fluid (CSF) studies revealed an elevated intracranial pressure, a white blood cell count of 7644 mm 3 , red blood cells 10,000 mm 3 , protein 440 mg/dl and glucose 20 mg/dl. Serum glucose was 102 mg/dl.…”
Section: Introductionmentioning
confidence: 99%